(untitled) (Medico Legal Update, 2020)
The transmembrane tyrosine kinase receptor, HER2/ErbB2, has been a subject of many studies owing to its predictive and prognostic values and its being a target of antibody-mediated treatment. Retrospective evidence strongly proposes that the over expression of HER2 is related to reduced disease free and overall survival in node positive and perhaps also node negative breast cancers. Prospective attempts showed that antibodies to HER2 can form tumor responses in advanced breast cancer women which overexpress this molecule. The existence of forkhead box protein 3 (FOXP3) in cells of breast cancer is a subject of debate. We have systematically analyzed the FOXP3 expression in 20 breast carcinoma samples at transcript levels. Recent progresses in understanding breast cancer crosstalk, homing processes, tumor cell dormancy, premetastatic niche formation and finally recognition of their micromilieu cytokines, growth factors and chemokinesmight provide the foundation of developing targeted treatment plans potentially rendering primary carcinomas and their metastases more responsive to chemotherapies. The current review has focused on the deep connections between HER-2 and FoxP3 in context of considering the determination of both of these molecules together to rationalize or more personalize the future research directions leading to better treatment for women with breast carcinoma.